Preferences of Rusa timorensis to Grasses and Their Body Morphometry and Velvet Antler Characteristics - M Sudibyo; Y Santosa; B Masy'ud; T Toharmat (Faculty of Animal Science, Bogor Agricultural University, 2013)
Timor deer (Rusa timorensis) is a wild native animal to Indonesia. The stags produce a high economic value of velvet antler (VA). This study was designed to evaluate the feed preference, nutrient consumption, age and morphometric of deer in relation to their velvet antler product (weigth and length) and quality (mineral and amino acids). Five stags with three ages classes were offered 3 combinations of 4 grasses in a captive area. Grasses were offered for 3 periods of 12 consecutive days during velvet antler growth period. Velvet antlers were harvested at 36 days old and analysed for their chemical content. The result showed that Timor deer had different preference to the grasses offered. Deer had a high preference on the combination of Pennisetum purpureum, Commelina benghalensis, Hierochloe horsfieldii, and Sorghum caudatum. High intake of grasses increased body weight. The regresion equation between the weight or length of velvet antler withage (year) and girth size (cm) were: Y (velvet antler weight)= 0.43 + 0.03 (age), r2= 0.99, P<0.05, and Y (length of velvet antler) = 5.7 + 0.31 (girth size), r2= 0.99, P<0.05. Aspartic acid, glutamic acid, and proline content of velvel antler were high in the older deer. The older deer having high girth size had the higher quality of velvet antler.